Effect of Training and Work Concerning on Employee Performance at PT. Golden Oilindo Nusantara - Windi Yolanda Farisa (International Journal of Community Service & Engagement, 2022)
This study aims to investigate the effects of training and work discipline on employees' performance at PT Goulden Oilindo Nusantara. Sample were selected deploying the saturated sample technique. Data of 30 respondents were collected through a questionnaire and analyzed using the multiple linear regression method. The results of the investigation unveil that partially each of training and work discipline has a significant effect on employees' performance. Likewise, simultaneously training and work discipline have a significant effect on employees' performance. These empirical findings can provide benefits for PT Golden Oilindo Nusantara. The leader of the company should optimize the training and work discipline factors to enhance employees' performance.